Physical and Chemical Characteristics of Solid Wastes Disposed at Taman Beringin Landfill, Kuala Lumpur - Salleh, Mohd Nazeri (2003)
At present, the Kuala Lumpur City Hall (KLCH) is facing problems in the disposal of their solid wastes due to the rapid increase in the amount generated as a result of rapid urbanisation. Existing landfill site at Taman Beringin is already exhausted and should be closed at any time. Due to this problem, there is a move to treat the solid wastes by thermal treatment technologies. Data on the characteristics of the solid waste is lacking and not reliable for the evaluation of these technologies. In addition, models for estimating the heating value based on the characteristics of Kuala Lumpur wastes are not available. This study was carried out to determine the characteristics and consequently develop the models for estimating the heating value of the Kuala Lumpur solid wastes. The study analyses and evaluates the physical and chemical characteristics of Kuala Lumpur solid wastes. The study was conducted at Taman Beringin Landfill from Mac 2000 to Jun 2000. A total of 26 samples were obtained from various sources including residential, commercial, institutional, cleansing and light industrial wastes. The truckload method was used for the sampling and characterising the physical components of wastes. The proximate and ultimate analysis of the wastes were also carried out.